2004
DOI: 10.1016/j.str.2004.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Mechanism of Ca2+ Activation of the Di-Heme Cytochrome c Peroxidase from Pseudomonas nautica 617

Abstract: Cytochrome c peroxidase (CCP) catalyses the reduction of H(2)O(2) to H(2)O, an important step in the cellular detoxification process. The crystal structure of the di-heme CCP from Pseudomonas nautica 617 was obtained in two different conformations in a redox state with the electron transfer heme reduced. Form IN, obtained at pH 4.0, does not contain Ca(2+) and was refined at 2.2 A resolution. This inactive form presents a closed conformation where the peroxidatic heme adopts a six-ligand coordination, hinderin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
70
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 47 publications
(1 reference statement)
8
70
1
Order By: Relevance
“…1B). This geometry is analogous to that observed in the PaCCP and PnCCP-OUT structures (8,10) but is lacking two additional water molecules between the calcium and the propionate of the high potential heme group that help complete the distorted pentagonal bipyramidal geometry seen in the other two structures. As in PaCCP and PnCCP, the charge of the calcium ion in RcCCP is not countered by negatively charged groups, suggesting that it can act as a modulator of electron transfer between the two heme domains.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…1B). This geometry is analogous to that observed in the PaCCP and PnCCP-OUT structures (8,10) but is lacking two additional water molecules between the calcium and the propionate of the high potential heme group that help complete the distorted pentagonal bipyramidal geometry seen in the other two structures. As in PaCCP and PnCCP, the charge of the calcium ion in RcCCP is not countered by negatively charged groups, suggesting that it can act as a modulator of electron transfer between the two heme domains.…”
Section: Resultssupporting
confidence: 55%
“…In the LP-heme, His-74 would be replaced by Met-118, whereas the HP-heme would lose its sixth ligand (Met-278). Structural data from several bacterial cytochrome c peroxidases and, in particular, recent studies on the P. nautica enzyme favor the first model (10). In that study the structure of the active form of PnCCP, termed PnCCP-OUT, reveals that the N-terminal heme group is penta-coordinated.…”
Section: Mutagenesis and Mechanistic Considerations; Structural Fleximentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, in bacterial enzymes containing more than one domain, such as bacterial cytochrome c peroxidase and nitrite reductase cytochrome cd 1 , it has been observed that reduction of the redox center in one of the domains implies a structural change in the protein [62][63][64][65]. Therefore, similar behavior cannot be ruled out for this enzyme and further experiments are currently in progress in our laboratory to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%